2013
DOI: 10.1108/03090561311285529
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate associations on consumer behaviour

Abstract: Purpose -In the present paper, the authors aim to study the relationship between corporate associations and loyalty by analyzing the role of identification with the company and satisfaction in this connection. Design/methodology/approach -The effects of corporate associations on consumers' loyalty were tested through a structural equation model for a sample of 781 financial services users. Findings -The results confirm the value of commercial expertise (CE) as one of the most important determinants of both con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(213 citation statements)
references
References 86 publications
11
194
3
5
Order By: Relevance
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A socially responsible company should strive to make profits, obey the law, be ethical, and be a good corporate citizen (Carroll, 1991, p. 43). This kind of CSR definition is known as the pyramid of CSR, and it is very accepted among researchers in this field and the most frequently cited in domestic and foreign literature (García de los Salmones, Herrero, & Rodríguez del Bosque, 2005;Ivanović-Đukić, 2011;Lee, Park, Rapert & Newman, 2012;Park, Lee & Kim, 2014;Perez, García de los Salmones, & Rodríguez del Bosque, 2012;Srbljinović, 2012), which is why this research is based on this definition of CSR. Some authors have suggested a different order in Carroll's pyramid due to different cultural, historical, and religious traditions (Crane, Matten, & Spence, 2006;Visser, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Section 4 contained five questions about the awareness of social capital, a concept proposed by [59,60]. Five additional questions in the survey related to consumer citizenship behavior as it pertains to participating in a sharing economy business that holds CSR values and that are also mentioned in [61,62]. All items used to assess the constructs employed a 5-point Likert scale [63], from strongly disagree (1) to strongly agree (5).…”
Section: Research Methods and Designmentioning
confidence: 99%